2020
DOI: 10.3389/fimmu.2020.02145
|View full text |Cite
|
Sign up to set email alerts
|

Re-analysis of Single Cell Transcriptome Reveals That the NR3C1-CXCL8-Neutrophil Axis Determines the Severity of COVID-19

Abstract: SARS-CoV-2 infection has recently been declared a pandemic. Some patients showing severe symptoms exhibit drastic inflammation and airway damage. In this study, we re-analyzed published scRNA-seq data of COVID-19 patient bronchoalveolar lavage fluid to further classify and compare immunological features according to the patient’s disease severity. Patients with severe symptoms showed DNA damage and apoptotic features of epithelial cells. Our results suggested that epithelial damage was associated with neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 23 publications
7
77
1
Order By: Relevance
“…Importantly, scRNA-sequence analysis showed that although NETosis genes were elevated in severe cases, they are considered abnormal when it comes to their antiviral effect. However, the same data revealed one mechanism through which neutrophil NETs might aggravate COVID-19 pathogenesis through epithelial damage [141] .…”
Section: Role Of Chemokines In Coronavirus Infectionsmentioning
confidence: 89%
See 2 more Smart Citations
“…Importantly, scRNA-sequence analysis showed that although NETosis genes were elevated in severe cases, they are considered abnormal when it comes to their antiviral effect. However, the same data revealed one mechanism through which neutrophil NETs might aggravate COVID-19 pathogenesis through epithelial damage [141] .…”
Section: Role Of Chemokines In Coronavirus Infectionsmentioning
confidence: 89%
“…This was further confirmed in a study which used single cell RNA sequencing analysis (scRNA-seq analysis) to compare the immunological response of severe and mild COVID-19 patients. The increase in CXCL8 release from myeloid cells was more pronounced in severe cases and was associated with an increase in neutrophil recruitment to the lungs along with an elevation in the number of neutrophils in the blood [141] . Moreover, higher expression of secretion-related molecules, lysosome-associated molecules, and NETosis features were observed in the neutrophils of severe patients [141] .…”
Section: Role Of Chemokines In Coronavirus Infectionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar to ARDS, patients with severe COVID-19 have a significant reduction in glucocorticoid receptor expression in bronchoalveolar lavage fluid myeloid cells that negatively related to lung neutrophilic inflammation, NETosis, and disease severity. 24,25 The dysregulated inflammation and coagulation observed in COVID-19 (see Pathophysiology) is also similar to that of multifactorial ARDS where ample evidence has demonstrated the ability of prolonged corticosteroid treatment (CST) to downregulate – systemic and pulmonary—inflammation-coagulation-fibroproliferation and accelerate disease resolution. 24,26 Additionally, the computed tomography findings of ground-glass opacities and the histological findings of organizing pneumonia, hyaline membranes, inflammatory exudates, and acute fibrinous and organizing pneumonia are all compatible with CST-responsive inflammatory lung disease.…”
Section: Methylprednisolone and Covid-19mentioning
confidence: 95%
“…The levels of monocyte-, neutrophil- and Th1-specific chemokines are directly proportional to the severity of COVID-19 infection ( Liao et al, 2020 ). CXCL8 was highly enriched in BALF from severe cases compared to healthy donors and mild cases of COVID-19, which correlated with abundant neutrophils in lungs of patients of that group ( Park and Lee, 2020 ). Transcriptome studies on BALF cells from COVID-19 patients also reveal that inflammatory innate and Th1-associated chemokines, their receptors and their signaling pathways are highly upregulated ( Gardinassi et al, 2020 ; Liao et al, 2020 ; Xiong et al, 2020 ; Zhou et al, 2020c ).…”
Section: Introductionmentioning
confidence: 93%